Glimpses of Unfamiliar Japan: Second Series - Hearn, Lafcadio, 1850-1904 (Salt Lake City, UT : Project Gutenberg, 2005)
"Glimpses of Unfamiliar Japan: Second Series" by Lafcadio Hearn is a collection of travel sketches written between 1890 and 1893. This work captures Hearn's impressionistic observations of Japanese culture, exploring themes of Buddhism, Shinto, and local folklore. Writing during Japan's reopening to the West, Hearn presents a mysterious, ancient civilization he feared would lose its charm through modernization and Western influence. His detailed accounts of Japanese lands, people, and traditions reflect both fascination and a desire to preserve what he saw as Japan's untouched essence. (This is an automatically generated summary.)
In a Japanese garden -- The household shrine -- Of women's hair -- From the diary of an English teacher -- Two strange festivals -- By the Japanese Sea -- Of a dancing-girl -- From Hoki to Oki -- Of souls -- Of ghosts and goblins -- The Japanese smile -- Sayonara!
Wikipedia page about this book: https://en.wikipedia.org/wiki/Glimpses_of_Unfamiliar_Japan
Release date is 2005-05-01
Produced by John Orford
Keywords: Japan -- Description and travel; Hearn, Lafcadio, 1850-1904 -- Homes and haunts -- Japan; Japan -- Religious life and customs